تفعيل دور المشاركة الشعبية والتمكين المستدام في التنمية المحلية - بركات, طارق (Latakia University Journal -Engineering Sciences Series, 2016)
تعدّ المشاركة الشعبية أحد الدعائم الرئيسية لعملية التنمية المحلية، حيث تتيح الفرصة أمام مختلف فئات المجتمع المحلي للمساهمة في إعداد وإدارة وتنفيذ خطط التنمية بما يتناسب مع احتياجاتهم وتطلعاتهم، والقيام بدور إيجابي في إنجاح المشروعات التنموية بشكل مستدام، بما يضمن تحقيق أهداف التنمية الوطنية الشاملة. وتتطلب المشاركة الحقيقية والفعالة اعتماد مبدأ التمكين المستدام لبناء القدرات الشعبية وتكريس الجهود والإمكانات البشرية لدى المجتمعات المحلية. في هذا السياق، يقدم البحث دراسة لمفهوم المشاركة الشعبية وأهميتها في التنمية المحلية، والتعرف على أساليب ومستويات المشاركة في العملية التنموية، شروطها، متطلباتها ومبادئها، كما يصنِّف درجات وصور المشاركة الشعبية خلال مراحل التنمية المحلية، إضافة إلى عرض التحديات التي تواجه المشاركة في عمليات التنمية المحلية. ويتناول البحث تحليلاً لأحد التجارب العالمية، والتي اعتمدت تطبيق مبدأ التمكين المستدام لتعزيز مساهمة المجتمع في تحقيق التنمية المستدامة بالبيئة العمرانية المحلية، من أجل استنتاج أهم مراحل ومعايير التمكين المستدام. يخلص البحث إلى جملة من النتائج والتوصيات تطمح إلى تعزيز الدور المهم للمشاركة الشعبية في التنمية المحلية، وذلك من خلال إيجاد آليات يمكن الاستعانة بها لتفعيل المشاركة على مستوى الوحدات المحلية، وكيفية التطبيق العملي لمبدأ تمكين المجتمعات في جميع مراحل عمليات التنمية المحلية، ليتم تقديم مجالات مختلفة للمشاركة الشعبية في أهم القضايا التنموية. The popular participation is one of the main pillars of the local development process, as it allows the opportunity for various community groups to contribute to the preparation, management and implementation of development plans in line with their needs and aspirations, and it has a positive role in making success of development projects in a sustainable manner, so as to ensure the achievement of the comprehensive national development objectives. A real and effective participation requires adoption of sustainable enablement principle to build the public capacity, and to devote the human potential and efforts of local communities. In this context, the researchpresents a study of the concept of popular participation and its importance in local development, and it identifies the methods and levels of participation in the development process, its conditions, requirements and principles, as classifieslevels and forms of popular participation during the phases of local development; in addition to presenting challenges ofthr participation in the local development processes. The research deals with an analysis ofone of global experiences thatapplies sustainable enablement principle, to enhance the contribution of the community in achieving sustainable development of the local urban environment, in orderto conclude the most important phases and criteria for sustainable enablement. The research concludes to a number of conclusions and recommendations aspires to promote the important role of public participation in local development, by creating mechanisms which could be used to activate participation at the level of localadministrative units, and exploring thepractical application way forenabling communities in all stages of the local development process, in order to provide different domains for popular participation in most important development issues.